Pengaruh kepuasan kerja dan komitmen organisasi terhadap Organizational Citizenship Behavior (OCB): studi kasus pada karyawan STMIK Indonesia Padang - Hesty Aisyah (Journal of Enterprise and Development (JED), 2020)
The goal of this study was to investigate the relationship between work satisfaction and organizational commitment and organizational citizenship behavior (OCB). The following is a case study of employees of STMIK Indonesia Padang in Padang, West Sumatra Province. Service quality will always be a critical aspect in improving corporate performance for organizations that place a high premium on customer pleasure. Because the quality of human resources within an organization has an effect on the quality of services supplied to consumers or clients, organizations must develop qualified and effective human resources. It is thought that human resources who demonstrate OCB conduct perform better. That is why firms must train their staff to exhibit ideal OCB behavior. This is a causal associative study that employs a quantitative technique. The data collection instrument was a questionnaire administered to a sample of 26 respondents, and the respondents were chosen using simple random sampling. The findings indicate that work satisfaction and organizational commitment have an effect on the OCB variable concurrently. Job satisfaction has a limited impact on the OCB variable. Meanwhile, organizational commitment has a major effect on employees' OCB.